Yhwh's battle against chaos in Ezekiel: the transformation of Judahite mythology for a new situation - Strine, C.A.; Crouch, C.L. (Society of Biblical Literature, 2013)
In addressing the theological crisis of the exile, Ezekiel relies on the mythology of the divine king who goes out to battle against the forces of chaos, commonly referred to as the Chaoskampf. This article explores how Ezekiel employs this imagery to reconfigure Yhwh’s relationships with Babylonia, Egypt, and Judah. In lieu of the now-defunct Judah, Ezekiel identifies the king of Babylon as Yhwh’s earthly agent for establishing order; Egypt is (re)confirmed as the exemplary human chaotic force, opposing Yhwh and his Babylonian agent; and Judah’s status is rendered a variable predicated on its political allegiances. Ezekiel’s scheme allows the native Judahite Chaoskampf theology to remain intact, at the expense of drastic changes to the relationship between the Judahite monarch and his patron deity, Yhwh.